Induction chemotherapy followed by definitive chemoradiotherapy versus chemoradiotherapy alone in esophageal squamous cell carcinoma: a randomized phase II trial - Shiliang Liu (Nature Portfolio, 2021)
The benefit of induction chemotherapy before definitive chemoradiotherapy (CRT) for patients with esophageal cancer is still uncertain. The results of this phase II randomized trial show that the addition of induction chemotherapy to CRT does not improve the response rate or survival of patients with unresectable esophageal squamous cell carcinoma.